The Lexical-Semantic Field of Impertinent Behaviour in Modern German - S. I. Lypka (Vasyl Stefanyk Precarpathian National University, 2016)
The article presents comprehensive research of the semantic field comprising different parts of speech denoting impertinent behaviour in modern German. The author uses a combination of system-centric and anthropocentric approaches to determine the nominative space covered by the constituents of the lexical-semantic field and to identify their systemic, syntagmatic, paradigmatic and epidigmatic characteristics. The semantic features of the systemic structure (i.e. the lexical-semantic field) are described with the help of formalized quantitative (approximate and static) methods.